Pengaruh Intergovernmental Revenue, Kekayaan Daerah dan Sisa Lebih Pembiayaan Anggaran terhadap Belanja Modal (Studi Empiris pada Kabupaten/Kota di Sumatra Barat) - Hikmah Fuji Astuti; Erinos NR (Jurnal Eksplorasi Akuntansi, 2021)
This study aims to examine the effect of intergovernmental revenue, regional wealht and financing surplus budget of capital expenditure. Population in this study were districts/cities in West Sumatera Province in 2015-2019. The analytical tool used in this study Is multiple linear regression analysis. The results of this study indicate that intergovernmental revenue and regional wealth has positive significant influence of capital expenditure. Financing surplus budget doesn’t significant influence of capital expenditure.